Adsorption and catalysis coupling integrated new material for removing formaldehyde as well as preparation method and application of adsorption and catalysis coupling integrated new material
By modifying the porous materials anionic surface and loading non-precious metal elements, a new adsorption catalytic coupling integrated material is prepared, which solves the problems of low formaldehyde removal efficiency and prone to secondary pollution in the prior art, and achieves an efficient and long-term formaldehyde purification effect.
Patent Information
- Application Number
- CN202510117254.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art has problems such as low efficiency in removing formaldehyde, which can easily lead to secondary pollution and difficulty in meeting strict limit standards.
Porous materials are used to modify the anionic surface and load non-precious metal elements (such as manganese and/or potassium), and new adsorption catalytic coupling integrated materials are prepared by in-situ synthesis method, and formaldehyde is removed by synergistic action of physical adsorption and catalytic degradation.
It has achieved thorough and long-term purification of formaldehyde, significantly improved the purification efficiency and long-term effectiveness of the material, and can quickly and efficiently remove formaldehyde at room temperature, meeting the requirements for effective formaldehyde removal in indoor environments for a long time.
Smart Images

Figure CN119869452A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of production technology of new adsorption-catalysis coupling integrated materials, and in particular relates to a new adsorption-catalysis coupling integrated material for removing formaldehyde, and a preparation method and application thereof. Background Art
[0002] With the continuous progress of society and the continuous improvement of the quality of life, the problem of residential air pollution caused by factors such as excessive indoor decoration has become increasingly prominent. Formaldehyde, as one of the main gaseous pollutants in indoor areas, has become the focus of public attention due to its long volatilization cycle and significant harmfulness. Studies have shown that formaldehyde not only damages the human respiratory and digestive systems, but long-term exposure may also cause systemic health problems and increase the risk of malignant tumors such as nasopharyngeal cancer, nasal and paranasal sinus tumors, and leukemia. In view of its serious health threat, formaldehyde has been clearly classified as a Class 1 carcinogen by the International Agency for Research on Cancer (IARC).
[0003] In response to this challenge, countries and environmental protection agencies have introduced stricter formaldehyde concentration limit standards. In the GB / T 18883-2022 standard officially implemented in China in 2023, the formaldehyde limit value will be increased from 0.1mg / m 3 Further reduced to 0.08 mg / m 3 The US Environmental Protection Agency (EPA) has also set an upper limit for formaldehyde concentration, requiring it not to exceed 0.027ppm. In addition, Japan's JISA 1901 standard and Europe's EN 16516 standard have also made strict regulations on indoor formaldehyde concentration. It can be seen that the problem of excessive formaldehyde has attracted great attention worldwide.
[0004] In this context, it has become an urgent task to effectively control indoor formaldehyde pollution using advanced technologies. Activated carbon adsorption technology has been widely used in the field of air purification due to its high efficiency and cost-effectiveness. However, activated carbon adsorbents are prone to saturation, and their physical adsorption effect is weak and easily affected by temperature fluctuations, resulting in the release of adsorbed formaldehyde again, causing secondary pollution. In addition, the removal effect of activated carbon on low-concentration formaldehyde is not ideal. Faced with increasingly stringent formaldehyde limit standards, a single activated carbon adsorption method can no longer meet people's needs. Therefore, it is particularly important to explore more efficient and stable formaldehyde control technologies.
[0005] In the prior art, CN 111013533 A discloses a method for preparing modified activated carbon for purifying formaldehyde. The preparation method comprises: first drying the activated carbon for standby use, and then preparing a certain concentration of oxidant and nucleophilic addition agent solution respectively; the oxidant solution and the dried activated carbon are fully mixed by an equal volume impregnation method, air-dried at room temperature, and vacuum dried to obtain oxidant-modified activated carbon; the nucleophilic addition agent solution and the oxidant-modified activated carbon are fully mixed by an equal volume impregnation method, air-dried at room temperature, and vacuum dried to obtain the final modified activated carbon. However, in this preparation method, the loading process is complicated and the cycle is long, the industrial production efficiency is low, and it is not conducive to actual industrial production. Moreover, the principle of purifying formaldehyde is to convert the oxidant and the nucleophilic addition agent into harmless substances through chemical reaction with formaldehyde. The oxidant and the nucleophilic addition agent will be continuously consumed in the process, and the long-term formaldehyde removal effect cannot be guaranteed. Summary of the invention
[0006] In order to solve the above technical problems, the present invention proposes a new adsorption-catalysis coupled integrated material for removing formaldehyde, and a preparation method and application thereof.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a new adsorption-catalysis coupled integrated material for removing formaldehyde comprises the following steps:
[0009] The porous material is subjected to anion surface modification and then dried, and then the obtained porous material carrier is used to load non-precious metal elements, so as to obtain the adsorption-catalysis coupling integrated new material for removing formaldehyde;
[0010] The non-noble metal elements include manganese and / or potassium.
[0011] Preferably, the porous material is activated carbon, molecular sieve, diatomaceous earth or alumina beads.
[0012] Beneficial effects: The present invention adopts an in-situ synthesis method to modify the non-precious metal catalyst loaded on the porous material to prepare a new adsorption-catalysis coupling integrated material for removing formaldehyde. The purification material of the present invention first utilizes the strong physical adsorption capacity of the porous material to quickly adsorb the formaldehyde molecules in the air on the porous material. Subsequently, the formaldehyde molecules adsorbed on the porous material are degraded under the action of the non-precious metal catalyst loaded on the porous material to generate substances that are harmless to the human body, thereby achieving harmless transformation of pollutants and in-situ regeneration of the porous material, thereby achieving a thorough and long-lasting purification effect on formaldehyde. The new adsorption-catalysis coupling integrated material with an eggshell-shaped structure provided by the present invention has a synergistic purification effect of catalytic oxidation and rapid adsorption on formaldehyde, thereby greatly improving the purification efficiency of formaldehyde, and while achieving a rapid and efficient removal effect on formaldehyde, significantly improving the long-term effectiveness of the purification material.
[0013] Preferably, the modifier used in the anionic surface modification process is one of nitric acid, oxalic acid, sodium hydroxide and hydrogen peroxide; and / or,
[0014] The concentration of the modifier is 0.1-1 mol / L.
[0015] Preferably, the temperature of the anionic surface modification is 30-90° C. and the time is 2-8 h.
[0016] Beneficial effects: The present invention modifies the surface anions of porous materials under appropriate conditions, which can open some closed micropores on the surface of porous materials, increase the specific surface area, and thus expose more active sites. These active sites can enhance the interaction between porous materials and other substances, improve their adsorption, catalytic and other properties, and can also adjust the charge distribution and properties on the surface of porous materials to better combine with manganese ions and potassium ions to increase the loading capacity.
[0017] Preferably, the loading of non-precious metal elements comprises the following steps:
[0018] The non-precious metal compound and the porous material carrier are heated and stirred in water for absorption, and then a reducing agent is added for heating reaction. After the reaction is completed, an interlayer water structure in the active component is constructed to obtain the new adsorption-catalysis coupling integrated material for removing formaldehyde.
[0019] Beneficial effects: The present invention utilizes redox reaction to generate catalytically active components in situ on the surface of porous materials, which simplifies the preparation process compared with the traditional impregnation loading method. In addition, since the reaction in the present invention is an exothermic reaction, the input of external energy can be saved during the reaction process, achieving energy-saving effects, helping to improve production efficiency and reduce production costs.
[0020] Preferably, the non-precious metal compound includes potassium permanganate and also includes one or more of potassium sulfate, potassium chloride, potassium persulfate and potassium carbonate; the mass ratio of the non-precious metal compound to the porous material carrier is 1:(5-20).
[0021] Preferably, the reducing agent includes one or more of ammonium oxalate, manganese sulfate and manganese nitrate.
[0022] Beneficial effect: When only potassium permanganate is used as a non-metallic compound, the present invention not only loads manganese elements, but also a small amount of potassium elements. By further adding an additional potassium salt additive, the loading amount of potassium ions in the active components of the catalyst can be increased, thereby promoting the cluster growth of δ-MnO2 on the carrier surface, stabilizing the interlayer water structure of the δ-MnO2 crystal form, and exposing more abundant active sites. The δ-MnO2 generated by the reaction in the present invention is a birnessite manganese dioxide substance with a layered structure, also known as active manganese. Its layered structure is formed by alternating arrangement of Mn atoms and oxygen atoms, and the layers are connected by oxygen atoms. It has a large specific surface area, rich active centers, and abundant unsaturated electron holes, which can activate oxygen and water in the air to generate active oxygen and active hydroxyl groups, thereby completing the rapid catalytic degradation of formaldehyde.
[0023] Preferably, the temperature of the heating and stirring absorption is 20-100° C. and the time is 1-6 hours; and / or,
[0024] The heating reaction is carried out at a temperature of 50-100°C and for a time of 6-24 hours.
[0025] Preferably, the temperature for constructing the interlayer water structure in the active component is 30-150°C, the heating rate is 1-10°C / min, and the time is 6-72h.
[0026] Beneficial effects: The interlayer water molecules of the δ-MnO2 generated in the present invention are connected to the oxygen atoms on the layer plate through hydrogen bonds, and the presence of the interlayer water plays a vital role, including maintaining the stability of the layered structure, expanding the channel size and increasing the mass transfer rate. By constructing its interlayer water structure through a suitable drying process, while ensuring that the interlayer water structure is not destroyed, the unbound water on the catalyst surface is removed, which can improve its catalytic performance and extend its service life.
[0027] A new adsorption-catalysis coupling integrated material for removing formaldehyde prepared by the above-mentioned preparation method, wherein the new adsorption-catalysis coupling integrated material has an eggshell structure.
[0028] A new adsorption-catalysis coupled integrated material for removing formaldehyde is used for its application in removing formaldehyde.
[0029] Compared with the prior art, the present invention has the following advantages and technical effects:
[0030] The preparation process of the adsorption-catalysis coupling integrated new material with an eggshell structure provided by the present invention is safe, simple, and low-cost, and can be industrially mass-produced. At the same time, it can be widely used in air purifier filter elements to replace traditional porous materials. And the obtained product can achieve the removal of formaldehyde at room temperature, and the formaldehyde concentration can be reduced from 1.0ppm to the national standard value of 0.06ppm within 15min under room temperature conditions, and the formaldehyde concentration can be reduced from 1.0ppm to 0.03ppm within 60min, and the activity effect is excellent. The experimental results show that the adsorption-catalysis coupling integrated new material obtained by the present invention has the purification effect of rapid capture and adsorption, catalytic oxidation, self-activation release of adsorption sites, and re-adsorption of formaldehyde gas, and has good long-term effectiveness, which can meet the requirements of long-term effective removal of formaldehyde in indoor environments and meet the purification requirements of long formaldehyde release cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0032] Figure 1 The scanning electron micrographs of K / Mn / AC-1 obtained in Example 1 and AC-pretreated obtained in Comparative Example 1;
[0033] Wherein, ac is the SEM image of K / Mn / AC-1, and df is the SEM image of AC-pretreatment;
[0034] Figure 2 This is a comparison chart of the formaldehyde removal activity of the potassium-doped manganese-based modified activated carbon materials obtained in Examples 1-3;
[0035] Figure 3 The activated carbon materials obtained in Examples 4-6 and Comparative Examples 1 and 2 were 3 Activity evaluation results of formaldehyde removal in cabins;
[0036] Figure 4 The modified activated carbon materials obtained in Examples 1 and 4 were heated to 3 m 3 Comparison of activity evaluation results for formaldehyde removal in a closed test chamber;
[0037] Figure 5 The results of the degradation activity of Mn / AC-4 obtained in Example 4 on formaldehyde under different wind speed conditions;
[0038] Figure 6 The potassium-doped manganese-based modified activated carbon material obtained in Examples 7-9 was heated to 3 m 3 Activity evaluation results of formaldehyde removal in cabins;
[0039] Figure 7The stability test results of the long-term formaldehyde removal activity of K / Mn / AC-1 obtained in Example 1 and the spare activated carbon carrier obtained in Comparative Example 1 are compared. DETAILED DESCRIPTION
[0040] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0042] The embodiment of the present invention provides a method for preparing a new adsorption-catalysis coupled integrated material for removing formaldehyde, comprising the following steps:
[0043] The porous material is subjected to anion surface modification and then dried, and then the obtained porous material carrier is used to load non-precious metal elements, so as to obtain the adsorption-catalysis coupling integrated new material for removing formaldehyde;
[0044] The non-noble metal elements include manganese and / or potassium.
[0045] Preferably, the porous material is activated carbon, molecular sieve, diatomaceous earth or alumina beads.
[0046] The present invention adopts an in-situ synthesis method to modify the non-precious metal catalyst loaded on the porous material to prepare an adsorption-catalysis coupling integrated new material for removing formaldehyde. The purification material of the present invention first utilizes the strong physical adsorption capacity of the porous material to quickly adsorb the formaldehyde molecules in the air on the porous material. Subsequently, the formaldehyde molecules adsorbed on the porous material are degraded under the action of the non-precious metal catalyst loaded on the porous material to generate substances that are harmless to the human body, thereby achieving harmless conversion of pollutants and in-situ regeneration of the porous material, thereby achieving a thorough and long-lasting purification effect on formaldehyde. The adsorption-catalysis coupling integrated new material for removing formaldehyde provided by the present invention has a synergistic purification effect of catalytic oxidation and rapid adsorption on formaldehyde, thereby greatly improving the purification efficiency of formaldehyde, and while achieving a rapid and efficient removal effect on formaldehyde, significantly improving the long-term effectiveness of the purification material.
[0047] In a preferred embodiment, the modifier used in the anionic surface modification process is one of nitric acid, oxalic acid, sodium hydroxide and hydrogen peroxide; and / or,
[0048] The concentration of the modifier is 0.1-1 mol / L. If the concentration is higher than this, it will cause excessive corrosion of the material pores and affect its loading effect. If the concentration is lower than this, the surface roughness of the material will change limitedly and the chemical composition of the porous material cannot be effectively changed.
[0049] In a preferred embodiment, the temperature of the anionic surface modification is 30-90°C and the time is 2-8 hours. If the temperature or time is lower than this, the surface roughness of the material will change limitedly and the chemical composition of the porous material cannot be effectively changed. If it is higher, it will cause excessive corrosion of the material pores and affect its loading effect.
[0050] In a preferred embodiment, the loading of non-precious metal elements comprises the following steps:
[0051] The non-precious metal compound and the porous material carrier are heated and stirred in water for absorption, and then a reducing agent is added for heating reaction. After the reaction is completed, an interlayer water structure in the active component is constructed to obtain the new adsorption-catalysis coupling integrated material for removing formaldehyde.
[0052] In a preferred embodiment, the non-precious metal compound includes potassium permanganate, and also includes one or more of potassium sulfate, potassium chloride, potassium persulfate and potassium carbonate.
[0053] In a preferred embodiment, the reducing agent includes one or more of ammonium oxalate, manganese sulfate and manganese nitrate.
[0054] In a preferred embodiment, the temperature of the heated stirring absorption is 20-100°C, and the time is 1-6h; if the temperature or time is lower than this, the porous material carrier will not be fully combined with substances such as potassium permanganate, and the reactants cannot be evenly adsorbed into the pores on the surface of the material. If it is higher than this, the properties of the reactants will change and affect subsequent reactions.
[0055] and / or,
[0056] The heating reaction temperature is 50-100°C and the time is 6-24h. If the temperature or time is lower than this, the reaction will be incomplete and insufficient active components will not be loaded. If it is higher, active manganese species of the specified crystal form will not be generated, thus affecting the use effect.
[0057] In a preferred embodiment, the temperature for constructing the interlayer water structure in the active component is 30-150°C, the heating rate is 0-10°C / min, and the time is 6-72h. If the temperature or time is lower than this, the unbound water in the porous material will not be completely removed, affecting its adsorption and catalytic performance. If it is higher, the interlayer water structure in the active component will be destroyed, reducing its catalytic activity and stability.
[0058] An embodiment of the present invention further provides a new adsorption-catalysis coupling integrated material for removing formaldehyde, which is prepared by the above-mentioned preparation method, and the new adsorption-catalysis coupling integrated material has an eggshell structure.
[0059] The embodiment of the present invention also provides an application of a modified porous material in removing formaldehyde.
[0060] Unless otherwise specified, the raw materials in the examples of the present invention were purchased from commercial sources;
[0061] The original untreated activated carbon is common commercially available 800 iodine value coal-made columnar activated carbon.
[0062] Unless otherwise specified, the room temperature or normal temperature in the embodiments of the present invention refers to 25±3°C.
[0063] Example 1
[0064] A method for preparing a new adsorption-catalysis coupled integrated material for removing formaldehyde comprises the following steps:
[0065] (1) Weigh a certain amount of original untreated activated carbon, repeatedly rinse the activated carbon particles with clean water for more than 5 times until the water used to rinse the activated carbon particles becomes clear and no black scum appears, then put the rinsed activated carbon into a container, add a 1 mol / L nitric acid solution with a mass ratio of 4:1 to the activated carbon, and immerse it at a constant temperature of 90°C for 6 hours, then repeatedly rinse it with clean water until no acidic substances remain, and dry it at 110°C for 24 hours to obtain a spare activated carbon carrier.
[0066] (2) Weigh potassium permanganate and a spare activated carbon carrier in a mass ratio of 1:10 and place them in a container, add potassium sulfate solution (concentration of 0.05 mol / L) in a mass ratio of 4:1 to the spare activated carbon carrier, stir at 60°C for 2 hours to allow it to be fully absorbed, then add ammonium oxalate in a molar ratio of 1:1 to potassium permanganate, and then stir and react at 90°C for 14 hours. After the reaction is completed, rinse it clean and dry it at 150°C for 24 hours at a heating rate of 5°C / min to obtain a potassium-doped manganese-based modified activated carbon material, which is recorded as K / Mn / AC-1.
[0067] Example 2
[0068] A method for preparing a novel adsorption-catalytic coupling integrated material for removing formaldehyde, the only difference from Example 1 is that the drying temperature in step (2) is 30° C. and the drying time is 24 h, and a potassium-doped manganese-based modified activated carbon material is obtained, which is recorded as K / Mn / AC-2. The remaining process steps and parameters are the same as those in Example 1.
[0069] Example 3
[0070] A method for preparing a novel adsorption-catalytic coupling integrated material for removing formaldehyde, the only difference from Example 1 is that the drying temperature in step (2) is 80° C. and the drying time is 24 h, and a potassium-doped manganese-based modified activated carbon material is obtained, which is recorded as K / Mn / AC-3. The remaining process steps and parameters are the same as those in Example 1.
[0071] Example 4
[0072] A method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde, which differs from Example 1 only in that step (2) includes the following steps:
[0073] (2) Weigh potassium permanganate and a spare activated carbon carrier in a mass ratio of 1:10 and place them in a container, add water in a mass ratio of 4:1 to the spare activated carbon carrier, stir at 60°C for 2 hours to fully absorb it, then add ammonium oxalate in a molar ratio of 1:1 to potassium permanganate, and then stir and react at 90°C for 14 hours. After the reaction is completed, rinse and dry at 150°C for 24 hours. A manganese-based modified activated carbon material is obtained, which is recorded as Mn / AC-4. The remaining process steps and parameters are the same as those in Example 1.
[0074] Example 5
[0075] A method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde is different from Example 4 only in that the mass ratio of potassium permanganate to the spare activated carbon carrier is 1:5, and a manganese-based modified activated carbon material is prepared, which is recorded as Mn / AC-5. The remaining process steps and parameters are the same as those in Example 4.
[0076] Example 6
[0077] A method for preparing a new adsorption-catalytic coupling integrated material for removing formaldehyde is different from Example 4 only in that the mass ratio of potassium permanganate to the spare activated carbon carrier is 1:20, and a manganese-based modified activated carbon material is prepared, which is recorded as Mn / AC-6. The remaining process steps and parameters are the same as those in Example 4.
[0078] Example 7
[0079] A method for preparing a new adsorption-catalysis coupled integrated material for removing formaldehyde comprises the following steps:
[0080] (1) Weigh a certain amount of original untreated activated carbon, repeatedly rinse the activated carbon particles with clean water for more than 5 times until the water used to rinse the activated carbon particles becomes clear and no black scum appears, then put the rinsed activated carbon into a container, add a 1 mol / L oxalic acid solution with a mass ratio of 4:1 to the activated carbon, and immerse it at a constant temperature of 30°C for 8 hours, then repeatedly rinse it with clean water until no acidic substances remain, and dry it at 110°C for 24 hours to obtain a spare activated carbon carrier.
[0081] (2) Weigh potassium permanganate and a spare activated carbon carrier in a mass ratio of 1:10 and place them in a container, add potassium persulfate solution (concentration of 0.05 mol / L) in a mass ratio of 4:1 to the spare activated carbon carrier, stir at 60°C for 6 hours to allow it to be fully absorbed, then add manganese nitrate in a molar ratio of 1:1 to potassium permanganate, and then stir and react at 50°C for 6 hours. After the reaction is completed, rinse it clean and dry it at 80°C for 24 hours at a heating rate of 1°C / min to obtain a potassium-doped manganese-based modified activated carbon material, which is recorded as K / Mn / AC-7.
[0082] Example 8
[0083] A method for preparing a new adsorption-catalysis coupled integrated material for removing formaldehyde comprises the following steps:
[0084] (1) Weigh a certain amount of original untreated activated carbon, repeatedly rinse the activated carbon particles with clean water for more than 5 times until the water used to rinse the activated carbon particles becomes clear and no black scum appears, then put the rinsed activated carbon into a container, add a 1 mol / L sodium hydroxide solution with a mass ratio of 4:1 to the activated carbon, and immerse it at a constant temperature of 50°C for 6 hours, then repeatedly rinse it with clean water until no acidic substances remain, and dry it at 110°C for 24 hours to obtain a spare activated carbon carrier.
[0085] (2) Weigh potassium permanganate and a spare activated carbon carrier in a mass ratio of 1:10 and place them in a container, add a potassium chloride solution (concentration of 0.05 mol / L) in a mass ratio of 4:1 to the spare activated carbon carrier, stir at 60°C for 1 hour to allow it to be fully absorbed, then add manganese sulfate in a molar ratio of 1:1 to potassium permanganate, and then stir and react at 60°C for 6 hours. After the reaction is completed, rinse it clean, and dry it at 120°C for 12 hours at a heating rate of 10°C / min to obtain a potassium-doped manganese-based modified activated carbon material, which is recorded as K / Mn / AC-8.
[0086] Example 9
[0087] A method for preparing a new adsorption-catalysis coupled integrated material for removing formaldehyde comprises the following steps:
[0088] (1) Weigh a certain amount of original untreated activated carbon, repeatedly rinse the activated carbon particles with clean water for more than 5 times until the water used to rinse the activated carbon particles becomes clear and no black scum appears, then put the rinsed activated carbon into a container, add a 1 mol / L hydrogen peroxide solution with a mass ratio of 4:1 to the activated carbon, and immerse it at a constant temperature of 90°C for 4 hours, then repeatedly rinse it with clean water until no acidic substances remain, and dry it at 110°C for 24 hours to obtain a spare activated carbon carrier.
[0089] (2) Weigh potassium permanganate and a spare activated carbon carrier in a mass ratio of 1:10 and place them in a container, add a potassium carbonate solution (concentration of 0.05 mol / L) in a mass ratio of 4:1 to the spare activated carbon carrier, stir at 60°C for 1 hour to allow it to be fully absorbed, then add manganese sulfate in a molar ratio of 1:1 to potassium permanganate, and then stir and react at 60°C for 6 hours. After the reaction is completed, rinse it clean, dry it at 80°C for 24 hours at a heating rate of 5°C / min, and obtain a potassium-doped manganese-based modified activated carbon material, which is recorded as K / Mn / AC-9.
[0090] Comparative Example 1
[0091] A method for preparing an activated carbon material, which differs from Example 1 only in that step (2) is not included, that is, the method comprises the following steps:
[0092] Weigh the activated carbon, rinse the activated carbon particles repeatedly with clean water for more than 5 times, until the water used to rinse the activated carbon particles becomes clear and no black scum appears, then put the rinsed activated carbon into a container, add a 1 mol / L nitric acid solution with a mass ratio of 4:1 to the activated carbon, and immerse it at a constant temperature of 90°C for 6h, then rinse it repeatedly with clean water until no acidic substances remain, and dry it at 110°C for 24h to obtain a spare activated carbon carrier, which is recorded as AC-pretreatment.
[0093] Comparative Example 2
[0094] A method for preparing an activated carbon material, which differs from Comparative Example 1 only in that it does not include the acid solution soaking step, that is, it specifically includes the following steps:
[0095] Weigh the activated carbon, rinse the activated carbon particles repeatedly with clean water for more than 5 times, until the water used to rinse the activated carbon particles becomes clear and no black scum appears, and dry it at 110°C for 24h to obtain the deashed activated carbon, which is recorded as AC.
[0096] Technical effects:
[0097] 1. The modified activated carbon material prepared in the embodiment of the present invention was tested for formaldehyde removal. The test conditions were as follows: according to the national standard GB-18204.2-2014, 300 g of the modified activated carbon material was placed in an air purifier (air volume: 250-300 m 3 / h) to 3m 3 A certain volume of formaldehyde solution is injected into the cabin, and the formaldehyde concentration is 1mg / m after volatilization and uniform mixing. 3 The formaldehyde removal rate test was carried out under the conditions of normal pressure, reaction temperature of 25°C, relative humidity of 40-60%, and cross-sectional flow rate of 1.8 m / s.
[0098] 2. In order to determine the degradation activity of the modified activated carbon material prepared in the embodiment of the present invention on formaldehyde under different wind speed conditions, the Mn / AC-4 prepared in Example 4 was taken in the experiment to determine its reaction activity when the purifier was turned on at different wind speeds. The other test conditions were the same as the formaldehyde removal test.
[0099] 3. In order to determine the stability of the long-term formaldehyde removal activity of potassium ion-doped manganese-based modified activated carbon materials, the K / Mn / AC-1 with the best activity was selected for cyclic testing, and the AC-pretreatment prepared in Comparative Example 1 was used for comparison. The test conditions are as follows: referring to the national standard GB / T18801-2022, the same mass (300g) of K / Mn / AC-1 and AC-pretreatment were placed in an air purifier (air volume: 250-300m 3 / h) in 3m 3 The test is carried out in the chamber. Before the cyclic test begins, first verify the degradation effect of the fresh catalyst in removing formaldehyde within 1 hour in an environment of 1ppm. Immediately after completion, a certain amount of formaldehyde (30mg, 50mg, 75mg) is evenly added to the cubic chamber in batches within 8 hours. During this period, the purifier is always kept on. After completion, the purifier is turned off and left to stand for 16 hours. After that, the total amount added is subtracted from the remaining formaldehyde in the chamber to obtain the actual formaldehyde removal amount. After completing the above operations, continue to verify the degradation effect of the aged catalyst in removing formaldehyde within 1 hour in an environment of 1ppm. The above steps are a cyclic test.
[0100] Figure 2 The potassium-doped manganese-based modified activated carbon material prepared in Example 1-3 was heated to 3 m 3 The results of the activity evaluation of formaldehyde removal in the cabin. Figure 2 It can be seen that the potassium-doped manganese-based modified activated carbon materials prepared at three different drying temperatures have similar formaldehyde removal activities and can reduce the formaldehyde in the cabin to the national standard value (0.08 mg / m 3 ) below, the formaldehyde removal efficiency within 60 min is about 97%, indicating that the modified activated carbon material has excellent formaldehyde removal rate and effect.
[0101] Figure 3 The activated carbon materials prepared in Examples 4-6 and Comparative Examples 1 and 2 were heated to 3 m 3 The results of the activity evaluation of formaldehyde removal in the cabin. Figure 3 It can be seen that manganese loading not only improves the formaldehyde removal activity of activated carbon materials, but also greatly increases the formaldehyde adsorption rate in the early stage of the reaction. The three manganese-based modified activated carbons with different loading ratios all showed good formaldehyde removal effects, and the formaldehyde removal efficiency within 60 minutes exceeded 96%.
[0102] Figure 4The modified activated carbon materials prepared in Examples 1 and 4 were heated to 3 m 3 Comparison of the results of the activity evaluation of formaldehyde removal in a closed test chamber. Figure 4 It can be seen that within the initial 5 minutes of the reaction, the formaldehyde removal rate of Mn / AC-4 was 81.6%, while the removal rate of K / Mn / AC-1 was 89.1%, which shows that the doping of potassium ions is beneficial to the rapid reduction of formaldehyde in the initial stage of the reaction. After 1 hour, the difference between the two is not large, and both can achieve a formaldehyde removal rate of more than 97%.
[0103] Figure 5 The results of the degradation activity of the manganese-based modified activated carbon material Mn / AC-4 under different wind speed conditions on formaldehyde prepared in Example 4 are shown. It can be seen that in the first 10 minutes of the initial reaction, as the wind speed of the purifier increased from 1.2m / s to 1.8m / s, the formaldehyde removal effect of Mn / AC-4 gradually increased. At the 5th minute of the reaction, when the wind speed of the purifier increased from 1.2m / s to 1.8m / s, the formaldehyde removal rate of Mn / AC-4 also increased from 71.04% to 76.69%, an increase of 5.65%.
[0104] Figure 6 The potassium-doped manganese-based modified activated carbon material prepared in Examples 7-9 was heated to 3 m 3 Activity evaluation results of formaldehyde removal in cabins. Figure 6 It can be seen that the manganese-based modified activated carbon materials prepared under different modifiers, different potassium salt doping and different reducing agents all have excellent formaldehyde removal activity, and can reduce the formaldehyde in the cabin to the national standard value (0.08 mg / m 3 ), and the formaldehyde removal efficiency was more than 92% within 60 min, indicating that the modified activated carbon material has excellent formaldehyde removal rate and effect.
[0105] Figure 7 The stability test results of the long-term formaldehyde removal activity of the potassium ion-doped manganese-based modified activated carbon material prepared in Example 1 and the spare activated carbon carrier prepared in Comparative Example 1 are compared. It can be seen that the cycle test is divided into three stages, and the total amount of formaldehyde added in the three different stages is not equal, and 30 mg, 50 mg, and 75 mg are added by a single injection method within 8 hours. The analysis is as follows:
[0106] (1) At the 30 mg / 8 h stage: K / Mn / AC-1 and AC-pretreatment were tested for 16 days and 7 days of continuous cycling, respectively. The results show that AC-pretreatment does not have the performance of catalytic oxidation of formaldehyde, and its formaldehyde performance continues to decay in 7 consecutive cycle tests. This is because there are a large number of HCHO molecules in its pores, resulting in adsorption saturation. In the test on the 7th day, the formaldehyde removal rate was only 58.9%, and the cumulative formaldehyde treatment amount was only 157.67 mg. It can be seen from the figure that AC-pretreatment has weak formaldehyde removal ability due to weak physical adsorption, and it is very easy to adsorb saturation and incomplete purification, which is also the pain point of activated carbon materials at present; K / Mn / AC-1 shows extremely excellent formaldehyde removal ability. In the continuous test for 16 days, K / Mn / AC-1 can always maintain its activity in formaldehyde removal, and its 1h formaldehyde degradation test can be maintained at more than 92%, which shows that the active components on the surface of K / Mn / AC-1 play a decisive role in extending the durability of activated carbon materials.
[0107] (2) At the 50 mg / 8 h stage: Since K / Mn / AC-1 can always maintain its activity in removing formaldehyde at an injection rate of 30 mg / 8 h, in order to further explore the removal of formaldehyde under high concentrations, the formaldehyde injection amount in a single cycle test was increased to 50 mg / 8 h, and the test was carried out for 9 days. The results show that compared with the formaldehyde degradation test on the 15th day, the 1h removal rate on the 16th day test dropped significantly, and the 1h removal rate was 89.6%. The possible reason is that the excessive formaldehyde caused the treatment capacity of K / Mn / AC-1 to decline, and too much formaldehyde was adsorbed in the pores, and the limited active components could not degrade the formaldehyde in time. Therefore, after completing the test on the 17th day, it was left to stand for 24 hours to achieve the regeneration of the active components. The results showed that in the test on the 19th day, the 1h removal rate of K / Mn / AC-1 recovered to 94.1%, which indicates that the active components on the surface of K / Mn / AC-1 can gradually consume or decompose the formaldehyde adsorbed inside the particles, thereby releasing more physical adsorption sites and having a certain self-activation ability. In the subsequent continuous tests of 22 to 24 days, it was found that the 1h removal rate had a significant attenuation, which was 90.2%, 89.1%, and 79.5% respectively. This indicates that the treatment capacity of K / Mn / AC-1 decreased at a sustained rate of 50 mg / 8 h, indicating an imbalance in the catalytic-adsorption synergy.
[0108] (3) At the 75 mg / 8 h stage: The performance of K / Mn / AC-1 was tested by further increasing the amount of formaldehyde added. The results showed that the 1 h removal rate decreased significantly. The 1 h removal rates were 73.3% and 73.9% in the tests on the 25th and 26th days. After 24 h of standing, the activity only recovered to 79.7%. In the test on the 31st day, the 1 h removal rate further decayed to 69%.
[0109] After 31 days of continuous experiments, it was shown that K / Mn / AC-1 has excellent formaldehyde removal ability, with a cumulative removal amount of 1255mg. It can maintain stable activity in the 30mg / 8h test. In the 50mg / 8h and 75mg / 8h tests, due to the excessive addition, the MnO2 on the surface of the activated carbon cannot decompose the excess formaldehyde into H2O and CO2 in time, which leads to saturation and a decrease in adsorption performance, resulting in a decrease in the 1h removal rate. When in the static stage, MnO2 can continuously decompose the excess formaldehyde, so that the formaldehyde adsorbed inside K / Mn / AC-1 gradually decreases, thereby restoring activity.
[0110] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde, characterized in that: The following steps are involved: The porous material is subjected to anion surface modification and then dried, and then the obtained porous material carrier is used to load non-precious metal elements, so as to obtain the adsorption-catalysis coupling integrated new material for removing formaldehyde; The non-noble metal elements include manganese and / or potassium.
2. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 1, characterized in that: The modifier used in the anionic surface modification process is one of nitric acid, oxalic acid, sodium hydroxide and hydrogen peroxide; and / or, The concentration of the modifier is 0.1-1 mol / L.
3. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 1, characterized in that: The temperature of the anion surface modification is 30-90° C. and the time is 2-8 hours.
4. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 1, characterized in that: The loading of non-precious metal elements comprises the following steps: The non-precious metal compound and the porous material carrier are heated and stirred in water for absorption, and then a reducing agent is added for heating reaction. After the reaction is completed, an interlayer water structure in the active component is constructed to obtain the new adsorption-catalysis coupling integrated material for removing formaldehyde.
5. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 4, characterized in that: The non-precious metal compound includes potassium permanganate, and also includes one or more of potassium sulfate, potassium chloride, potassium persulfate and potassium carbonate; the mass ratio of the non-precious metal compound to the porous material carrier is 1: (5-20).
6. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 4, characterized in that: The reducing agent includes one or more of ammonium oxalate, manganese sulfate and manganese nitrate.
7. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 4, characterized in that: The heating, stirring and absorbing process is performed at a temperature of 20-100°C and a time of 1-6 hours; and / or, The heating reaction is carried out at a temperature of 50-100°C and for a time of 6-24 hours.
8. The method for preparing a new adsorption-catalysis coupling integrated material for removing formaldehyde according to claim 4, characterized in that: The temperature for constructing the interlayer water structure in the active component is 30-150° C., the heating rate is 1-10° C. / min, and the time is 6-72 hours.
9. The new material of adsorption-catalysis coupling obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The new adsorption-catalysis coupling integrated material has an eggshell structure.
10. Use of the new adsorption-catalysis coupling integrated material as claimed in claim 9 in removing formaldehyde.
Citation Information
Patent Citations
In-situ preparation method, product and application of bifunctional material
CN107583608A
Surface-modified carbon and sorbents for improved efficiency in removal of gaseous contaminants
CN109963639A
Manganese dioxide modified activated carbon composite adsorbent, preparation method thereof and application in arsenic removal
CN112058232A
Formaldehyde purification porous film and preparation method thereof
CN112774652A
Formaldehyde adsorption-catalytic decomposition composite material, preparation method and application
CN112774653A